Mindfulness Training: Can It Create Superheroes? - Jones, Patrick (Frontiers in Psychology, 2019)
With the emergence of the science of heroism there now exists both theoretical and empirical literature on the characteristics of our everyday hero. We seek to expand this inquiry and ask what could be the causes and conditions of a superhero. To address this we investigate the origins of mindfulness, Buddhist psychology and the assertion that its practitioners who have attained expertise in mindfulness practices can develop supernormal capabilities. Examining first their foundational eight “jhana” states (levels of attention) and the six consequent “abhinnas” (siddhis or special abilities) that arise from such mental mastery, we then explore any evidence that mindfulness practices have unfolded the supernormal potential of its practitioners. We found a growing base of empirical literature suggesting some practitioners exhibit indicators of enhanced functioning including elevated physical health and resistance to disease, increased immunity to aging and improved cognitive processing, greater resilience and fearlessness, more self-less and pro-social behaviours, some control over normally autonomic responses, and possibly some paranormal functionality. These improvements in normal human functioning provide some evidence that there are practices that develop these abilities, and as such we might want to consider adopting them to develop this capability. There remains however insufficient studies of expert meditators and more research of adepts is called for that explores the relationship between levels of attentional skill and increases in functionality. We propose in search of the superhero, that if conventional mindfulness training can already augment mental and physical capabilities, a more serious inquiry and translation of its advanced methods into mainstream psychological theory is warranted.